Ductile damage evolution law for proportional and non-proportional loading conditions (Fracture and Structural Integrity, 2018)
The characterization of ductile damage evolution, and its description, have been the object of extensive research in the continuum damage mechanic field. Many different models have been developed since the pioneering works carried out a few decades ago. In detail, the stress triaxiality and the Lode angle parameters have been identified as the two main variables that affect the material ductility. The literature offers a great number of investigations under monotonic loading conditions, however, a proper characterization of the damage evolution under cyclic loading or non-proportional loading is still missing.In this paper, an unconventional coupled elastoplastic and damage constitutive model with a Mohr-Coulomb failure criterion is presented. The novelty of this study is represented by the modification of the ductile damage law in order to consider the damage evolution under non-proportional loading conditions. Therefore, the idea is to investigate the structural response of a steel bridge column subjected to a cyclic non-proportional loading, showing how, a different approach in the description of the ductile damage evolution, is necessary for a realistic description of the pier behavior.
Keywords: Ductile damage; Elastoplasticity; Non-proportional loading; Damage Subloading Surface model